Miller–Payne Grading and 70-Gene Signature Are Associated With Prognosis of Hormone Receptor-Positive, Human Epidermal Growth Factor Receptor 2-Negative Early-Stage Breast Cancer After Neoadjuvant Chemotherapy - Wang, Liye; Luo, Rongzhen; Lu, Qianyi; Jiang, Kuikui; Hong, Ruoxi; Lee, Kaping; Zhang, Ping; Zhou, Danyang; Wang, Shusen; Xu, Fei (Frontiers in Oncology, 2021)
Introduction HR+/HER2− breast cancer (BC) has a much lower pathological complete response (pCR) rate to neoadjuvant chemotherapy (NAC). Therefore, to better stratify the relapse risk for HR+/HER2− non-pCR populations, it is essential to accurate identification new prognostic markers. Materials and Methods The study retrospectively analyzed 105 stage II–III patients who were diagnosed with HR+/HER2− BC and received NAC followed by breast and axilla surgery between 2013 and 2019 in Sun Yat-Sen University Cancer Center. The Miller–Payne (MP) grading system was used to evaluate pathological responses to NAC. The 70-gene signature was used to classify the prognosis signatures. Results Among the 105 patients, the study demonstrated that larger tumor size and lower progesterone receptor level at baseline and larger tumor size postoperative were statistically significantly associated with worse disease-free survival (DFS) (p = 0.004, p = 0.021, and p = 0.001, respectively). Among 54 patients who underwent the 70-gene assays, 26 (48.1%) had a low-risk signature; 28 (51.9%) patients had a high-risk signature. Patients with poor response (MP grades 1–2) were more likely to with a high-risk 70-gene signature than those with good response (MP grades 4–5). The final analysis showed that DFS was longer in the low-risk group than in the high-risk group [52.4 vs. 36.1 months of the median DFS, hazard ratio (HR) for recurrence, 0.29; 95% confidence interval (CI), 0.10–0.80; p = 0.018]. DFS was longer in the good response (MP grades 3–4) group than in the poor response (MP grades 1–2) group (94.7% vs. 60% of the patients free from recurrence; HR, 0.16; 95% CI, 0.05–0.47; p = 0.037). When stratified by MP grades combined with the 70-gene signature, subgroup analyses showed the good-response low-risk group with the best DFS, whereas the poor-response high-risk group showed the worst DFS (p = 0.048). Due to the short median follow-up time of 34.5 months (5.9–75.1 months), MP grades and the 70-gene signature did not show significant prognostic value for overall survival. Conclusion The study showed that analysis of MP grades combined with the 70-gene signature with residual NAC-resistant breast samples has a significant correlation with DFS.